Complicated Grief of Immediate Family Caregivers: A Concept Analysis. (July 2019) - Mason, Tina M.; Tofthagen, Cindy S.
Abstract : Grieving is a normal reaction to loss; however, not everyone is able to recover from grief and adjust to a life after the loss. "Complicated grief" (CG) is a term used to describe intense and prolonged bereavement after the loss of a loved one that interferes with normal activities accompanied by destructive thoughts and behaviors. In practice and research, the concept of CG varies in definition and instruments used to measure. This concept analysis examines relevant research related to CG experienced by caregivers to provide a clear, comprehensive definition. Implications for nursing practice and research are explored.